Policyholder Surrender Behavior in the Nepalese Life Insurance Market During the COVID-19 Pandemic - Ghimire, Rabindra; Thapa, Bharat Singh; Waikar, Vilas (Interdisciplinary Journal of Innovation in Nepalese Academia, 2024)
The Nepalese life insurance industry is facing a significant challenge due to its high surrender rate, which became particularly alarming during the COVID-19 pandemic. In this context, this study aims to explore the different reasons behind the life insurance policy surrenders and examine the association between the policy holding period and the demographic characteristics of policyholders. Primary data were collected during 2020-2021 through a questionnaire survey from 445 policyholders who had already surrendered the policy. The survey was conducted in eight major cities in Nepal. The findings reveal several key insights into policyholders’ surrender behavior. The most influential factors contributing to surrender include advice from family and friends, lack of knowledge about the policy, and insufficient information provided to policyholders. The study concludes that economic factors are the most significant driver of surrender behavior, followed by knowledge gaps, social influences, company-related factors, and, to a lesser extent, agent-related factors. Notably, no demographic variables were found to have a significant association with surrender reasons. The study recommends implementing tighter financial underwriting procedures, enhancing customer education and awareness about policies, and fostering stronger customer relationships to mitigate the incidence of policy surrenders.